Implementation One-Data Initiative and Network Relations between Actors in Maritime and Fisheries Field - Afini Mahabas (Kementerian Perencanaan Pembangunan Nasional (Bappenas), 2018)
This study aims to determine the inter-actor relationships at the Ministry of Marine Affairs of Fisheries (KKP) and outside the KKP in implementing the One Marine and Fishery Data system. The goal, of achieving unified standardized data are unified standardized metadata and a single data portal and the role of the actor in solving data issues that existed in the previous KKP. The approach adopted is to use a networking model to find out more about networking principles such as collective action, degree of sharing and interdependency. The research result states that network relations among the activity factors of the One Marine Fishery Data are driven more by the regulations that applied before. Although this is counterproductive to the spirit of network, interactor network relationships can be realized based on the characteristics of the network. It is also supported by strong leadership at the KKP. There is the need to improve coordination in communication, particularly with parties outside the KKP, strengthen strategies by network managers, and reframe perceptions of actors related to the objectives of the One Marine and Fishery Data so that networking relationships in these activities will grow.